A New Strain Collection for Improved Expression of Outer Membrane Proteins - Meuskens, Ina; Michalik, Marcin; Chauhan, Nandini; Linke, Dirk; Leo, Jack C. (Frontiers in Cellular and Infection Microbiology, 2017)
Almost all integral membrane proteins found in the outer membranes of Gram-negative bacteria belong to the transmembrane β-barrel family. These proteins are not only important for nutrient uptake and homeostasis, but are also involved in such processes as adhesion, protein secretion, biofilm formation and virulence. As surface exposed molecules, outer membrane β-barrel proteins are also potential drug and vaccine targets. High production levels of heterologously expressed proteins are desirable for biochemical and especially structural studies, but over-expression and subsequent purification of membrane proteins, including outer membrane proteins, can be challenging. Here, we present a set of deletion mutants derived from E. coli BL21(DE3) designed for the over-expression of recombinant outer membrane proteins. These strains harbor deletions of four genes encoding abundant β-barrel proteins in the outer membrane (OmpA, OmpC, OmpF and LamB), both single and in all combinations of double, triple and quadruple knock-outs. The sequences encoding these outer membrane proteins were deleted completely, leaving only a minimal scar sequence, thus preventing the possibility of genetic reversion. Expression tests in the quadruple mutant strain with four test proteins, including a small outer membrane β-barrel protein and variants thereof as well as two virulence-related autotransporters, showed significantly improved expression and better quality of the produced proteins over the parent strain. Differences in growth behavior and aggregation in the presence of high salt were observed, but these phenomena did not negatively influence the expression in the quadruple mutant strain when handled as we recommend. The strains produced in this study can be used for outer membrane protein production and purification, but are also uniquely useful for labelling experiments for biophysical measurements in the native membrane environment.